DEVELOPMENT OF PEDAGOGICAL IDEAS IN UZBEKISTAN DURING THE YEARS OF INDEPENDENCE. - U.U., Kurbanova (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes pedagogical research on the pedagogical features of organizing students' independent learning during the years of independence. independent work, independent study, independent work, independent learning, independent thinking.